Advancing smarter and more secure industrial applications using AI, IOT, and blockchain technology - Chelliah, Pethuru Raj; Saini, Kavita 1976- (IGI Global, 2021)
"This book articulates and accentuates various AI algorithms, fresh innovations in the IoT and blockchain spaces explaining how suggested AI algorithms come in handy in producing predictive and prescriptive insights out of big data
Includes bibliographical references and index
Chapter 1. Internet of things (IoT) and blockchain applications in pharmaceutical supply chain provenance to achieve traceability, transparency, and authenticity -- Chapter 2. Insights on the prospects of multi-access edge computing -- Chapter 3. Achieving ambient intelligence in addressing the COVID-19 pandemic using fog computing-driven IoT -- Chapter 4. Elaborative investigation of blockchain technology in intelligent networks -- Chapter 5. A proposed approach for building a SARS-COV-2 watch in the IoT network -- Chapter 6. Blockchain implementation using Python -- Chapter 7. An end-to-end video content encryption module for HLS video streaming -- Chapter 8. The industry 4.0 for secure and smarter manufacturing -- Chapter 9. Advanced associated defence in a cloud IoT environment -- Chapter 10. Recent trends in block chain technology: challenges and opportunities -- Chapter 11. Secure file storage in cloud computing using a modified cryptography algorithm -- Chapter 12. IoT applications for coronavirus industry protection: smart mask and smart badge -- Chapter 13. Reliable blockchain-aided searchable attribute-based encryption for cloud-IoT -- Chapter 14. Retail and Internet of things: a digital transformation -- Chapter 15. IoT-based smart gardening system using the cloud. - Mode of access: World Wide Web
Keywords: Blockchains (Databases) -- Industrial applications; Artificial intelligence -- Industrial applications; Internet of things -- Industrial applications